Problems of Moving Teachers in Using Independent Teaching Platforms as at Tool Environment Education in Schools - Syahriani Syahriani; Agung Purwanto; Setia Budi (Universitas Muhammadiyah Enrekang, 2023)
In an era of education that continues to develop, the role of the Driving Teacher lies not only in delivering lesson material but also in efforts to create a sustainable and environmentally oriented learning experience. The Merdeka Mengajar Platform (PMM) is a technology platform that accommodates motivating teachers to obtain references, inspiration, and understanding of the independent curriculum. Implementing the Merdeka Mengajar Platform has several areas for improvement, especially related to gaps in technological understanding. Driving teachers, especially in Jakarta, may need help with mastering the features provided by the platform. Based on the research results obtained in the field, the factors that hinder teachers from using PMM for environmental education in schools are time management, limitations in using technology, and workload. The Activator Teacher's process in applying Environmental Education material sourced from PMM is applying material obtained from PMM in the teaching and learning process in the classroom. Meanwhile, the obstacles to Mobilizing Teachers to carry out actual environmental education actions sourced from PMM are limited interaction in online learning and the need for access to natural resources and the school environment.